AKTIVITAS ANTIBAKTERI EKSTRAK DAUN LIDAH MERTUA (Sansivieria tirfasciata var.laurentii) TERHADAP BAKTERI Klebsilla pneumonia - Fitriani, Audiah; Sawitri, Nining Eka; Khatrina, Syahdapuan Dara; Nadifah, Fitri; Arisandi, Desto (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2024)
Background: Pneumonia is an acute infection of the lower respiratory tract characterized by coughing and shortness of breath caused by Klebsiella pneumoniae bacteria. Sansevieria contains flavonoids, saponins, alkaloids, and steroids known to have antibacterial properties that can destroy the bacterial cell walls. Objectives: This study aimed to determine the antibacterial activity of Sansevieria leaf extract against the growth of K. pneumoniae. Materials and Methods: Detection of antibacterial activity of Sansevieria was conducted with disc-diffusion test. The presence of antibacterial activity is indicated by the appearance of inhibition (clear) zone after applying the extract at a concentration of 60-100% to the culture medium. As a positive control, the antibiotic chloramphenicol was used. Results: The higher the extract concentration, the higher the inhibition zone formed. The inhibition zone formed from extract concentrations of 60%, 70%, 80% is classified as medium (d = 8; 8.5; 9 mm). Meanwhile, the inhibition zones at concentrations of 90% and 100% are 10.5 and 13.5 mm and are classified as strong. The clear zone of the positive control was 29 mm (very strong). Conclusions: Sansevieria leaf extract has the potential to inhibit the growth of K. pneumoniae bacteria.